PENGARUH QUALITY OF WORK-LIFE TERHADAP EMPLOYEE ENGAGEMENT PADA KARYAWAN ALFAMART - Pebrianti, Rika Indri (Jurnal Perspektif Bisnis, 2023)
Human resources are the main driver of a company, so the human resources system and organizational structure within the company need to be managed well. One effort in managing human resources so that they are able to work well is to create a quality work life. Quality work life is a management technique that includes a quality control group that expresses the importance of respect for humans in the work environment. This research explains the influence of quality of work life on Employee Engagement among Alfamart employees in Rajabasa District. The research method in this study used quantitative research with a sample of 90 Alfamart employees in Rajabasa District. Data collection techniques were carried out using observation, interviews, questionnaires and documentation, data analysis using simple linear regression and hypothesis testing. The research results explain that Quality work-life has a partial effect on Employee Engagement. Suggestions from the research results obtained, there is a need for further development of the variables of social integration and social relevance to employee engagement.